Sensitive performance-based assessment of everyday action in older and younger adults. Issue 2 (4th March 2018) - Rycroft, Sarah Seligman; Giovannetti, Tania; Divers, Ross; Hulswit, Jacob
ABSTRACT: Everyday function is compromised by mild cognitive changes in aging. These changes predict risk for future decline and dementia but remain poorly characterized, largely due to a scarcity of sensitive, objective measures.Twenty-seven younger adults and 25 non-demented older adults completed the Naturalistic Action Test (NAT), a performance-based measure of everyday action involving simple and complex tasks. Performance was coded for overt errors and subtle inefficiencies. Participants also completed self-report functional measures and cognitive tests. Mixed ANOVAs revealed that older adults made more subtle NAT errors with high task demands; groups did not differ in overt errors. Correlations did not reveal significant relations between self-report and NAT errors, but NAT performance was correlated with learning and recall.The NAT provides a promising tool for detecting subtle age-related changes and examining decline across levels of impairment. Self-report may lack sensitivity to subtle changes, and episodic memory changes underlie early functional disruption.